Analogy Between Learning Theories (Environmental, Innatist, and Interactionist) from the Perspective of Childhood with the Movie Matilda (1996) (REMUNOM, 2025)
The aim of this article is to draw an analogy between learning theories based on the theorists Burrhus Frederic Skinner (1904-1990) with the environmentalist theory; Jean-Jacques Rousseau (1712-1778) with the theory of innatism; Jean Piaget (1896-1980) and Lev Semenovich Vygotsky (1896-1934) with the theoretical conception of interactionism. Based on these theories, the article portrays the different conceptions of education presented in the film Matilda (1996), enabling an analogy. We know that families are different from one another, just as other figures responsible for the formation of every human being—parents, family, school, teachers, and society in general—have different perceptions both of the child and of childhood. Learning theories refer to ways of grasping the world, society, and human beings, providing us with a guide for what best adapts and consequently influences teaching and learning processes, such as environmentalism, which presents a directive pedagogy; innatism, which dictates a non-directive pedagogy; and interactionism, whose pedagogy is relational. Thus, the article seeks, through learning theories, to discuss how childhood is represented by different perceptions and educational practices, based on the examples presented by the characters in Matilda (1996), and to present the environmentalist, innatist, and interactionist conceptions, while reflecting on the concepts of childhood and infancies, with an emphasis on childhood as a social category. The article concludes with final considerations.